La hoja de coca en las fábricas de cocaína y el estanco de la coca en la región norte del Perú 1900 - 1950 - Alquizar Deza, Oscar Eduardo (2017)
The purpose of this research was the knowledge of the reality of the coca leaf in the_x000D_ northern region of Peru during the first half of the 20th century. Detailing the reality of_x000D_ the cocaine manufacturers in the city of Trujillo, who they were, who they traded with,_x000D_ how they produced, how the cocaine factories were distributed in the city. In the same_x000D_ way, we will specify in what districts of the region, the cultivation and harvesting of_x000D_ coca leaves was carried out, we provide an analysis of the uses that were given to the_x000D_ unique type of coca of the northern zone and hho was the driving force of the coca_x000D_ harvest. The spiritual and religious significance of coca in the Andean world was_x000D_ studied, and also its profane variant, the coca chewing (boleo) on the northern sugar_x000D_ plantations. The final part explains the changes that occurred in the whole production of_x000D_ coca because of the establishment of the Coca State Monopoly (Estanco) under the_x000D_ pressure of the emerging anti-drug policies in the international political scene.